DIFFERENCES IN ATTITUDES TOWARDS SPORT BETWEEN SECONDARY SCHOOL STUDENTS - Dževad Džibrić; Adnan Bukvić; Amer Hodžić; Tarik Ljubović; Dragiša Jovanović; Erko Solaković (Sport Scientific And Practical Aspects, 2025)
Sport is an extremely common activity that significantly affects the whole society. It has educational value and can be a powerful tool in education. Adopting values and developing attitudes towards sports is an extremely complex educational problem. This transversal research aimed to determine the differences in attitudes towards sports between students in different grades of high school. The population from which the sample of 349 respondents was taken was defined as the population of students of I, II, III, and IV grade of high schools from Zavidovići, male, aged 15-18 years ± 6 months. A survey questionnaire was used to assess attitudes about sports, which consisted of 25 items especially evaluated on a 5-point scale. To determine the differences in attitudes towards sports between students of different grades, the Kruskal Wallis test was applied. The obtained results showed that there are statistically significant differences between the treated groups in 18 particles. Most differences are present between the first and fourth grade (11), and the second and fourth grade (10). Minor differences are present between the second and third (3), third and fourth grade (3), and the first and second (2), first and third grade (2). From this, we see that there is a statistically significant difference in attitudes towards sports about age, and therefore it can be concluded that students entering older classes prefer sports, ie develop more negative attitudes towards sports.